(untitled) (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2019)
Blood culture in Intensive Care Units: prevalence, request profile and microbial susceptibility in a hospital in Southwestern Bahia state, Brazil